Behavioral Manifestations of Dark Personality Narcissism: an Indigenous Study on Indonesian Workers - Ningrum, Widya Dwi; Nuzulia, Siti (Journal of Social and Industrial Psychology, 2023)
Narcissism is one of the three traits incorporated in a dark personality, and this trait is described by an individual's tendency to dominate, like to be the center of attention and be self-oriented. Not only in individual cultural cultures, narcissism is also a fertile body in a collective society that upholds social harmony and behaves by values and norms in its group. Judging from these characteristics, it is suspected that there will be differences in the manifestations of narcissism in collective societies such as in Indonesia. Researchers conducted a study us images psychology collaborative descriptive quantitative research design to trace the form of behavioral images of narcissism in a collaborative culture. The sampling technique used was snowball sampling and involved as many as 760 worker respondents in Indonesia. The research findings were then analyzed using percentage descriptive techniques and categorization. This study succeeded in revealing several things, including (1) the positive and negative behavior of selfish individuals in the work environment; (2) the impact on personal and work relationships when dealing with narcissistic individuals in the work environment; (3) the most disliked behavior of narcissistic individuals in the work environment; and (4) how to deal with narcissistic individuals in the work environment.